Effects of air pollutants on morphology and reproduction in four lichen species in Córdoba, Argentina - Estrabou, Cecilia (2004)
The effects of contamination on morphological and reproductive parameters of four lichen species in two urban areas and a control site were studied. The four lichen species studied have all been previously identified as tolerant, resistant and sensitive to air pollution respectively. These species were sampled and collected from the bark of Melia azedarach L. (“paraíso”), situated in the cities of Córdoba, Río Cuarto and Río Ceballos. About 50 specimens for each species were removed. The following features were analyzed in each specimen: thallus color, cover and number of apothecia, soredia, necrosis of the thallus, changes in thallus size, thickness of lower and upper cortex, algae number and a fertility index was built. In Ramalina celastri, a sensitive species, darkening and reduction of thallus size, the presence of particulate matter and necrotic areas are some of the visible effects of air pollution. Physcia endochrysea, a resistant species, only shows minor changes in polluted areas. In resistant species, the fertility rate shows a marked reduction in polluted areas. In Canomaculina pilosa, a tolerant species, a reduction in thallus size and darkening of both the thallus and soredia is evident. Necrotic areas are particularly obvious with this species as well. Physcia undulata exhibits the fewest alterations and greatest growth in urban areas. The most variable feature was the thickness in the upper and the lower cortex. Algae number measured in lacunae along with he fertility index resulted good indicators.